Phytophthora oleae sp. nov. causing fruit rot of olive in southern Italy. (30th March 2018) - Ruano‐Rosa, D.; Schena, L.; Agosteo, G. E.; Magnano di San Lio, G.; Cacciola, S. O.
Abstract : A homothallic Phytophthora species was found to be consistently associated with a rot of mature fruits of two local cultivars of olive ( Olea europaea ) in Calabria, southern Italy. The phylogenetic analysis of sequences of the ITS1‐5.8S‐ITS2 region and cox1 gene enabled its identification as a new species of clade 2, with a basal position compared to previously described subclades. The new species is described formally with the epithet Phytophthora oleae, referring to the natural matrix from which it was isolated. A unique combination of molecular and morphological characters clearly separates P. oleae from other already described Phytophthora species. This new species produced semipapillate, occasionally bipapillate, persistent sporangia on simple sympodially branching sporangiophores as well as globose and smooth‐walled oogonia, paragynous antheridia and spherical, plerotic oospores. The pathogenicity of P. oleae was confirmed in inoculation trials on fruits of three olive cultivars, including the two local cultivars from which the pathogen had been isolated.